The alteration of intra-ligand donor-acceptor interactions through torsional connectivity in substituted Re-dppz complexes - Adams, Bethany; Shillito, Georgina E.; Salm, Holly van der; Horvath, Raphael; Larsen, Christopher B.; Lucas, Nigel T.; George, Michael W.; Gordon, Keith C. (American Chemical Society, 2017)
The ground and excited properties of a series of [ReCl(CO)3(dppz)] complexes with substituted donor groups have been investigated. Alteration of donor-acceptor communication through modulation of torsional angle and the number and nature of the donor substituent allowed the effects on the photophysical properties to be characterized though both computational and spectroscopic techniques, including TD-DFT, resonance Raman and time resolved infrared. The ground state optical properties show significant variation as a result of donor group modulation, with increased angle between the donor and acceptor blue-shifting and depleting the intensity of the lowest energy transition, which was consistently ILCT in nature. However, across all complexes studied there was minimal perturbation to the excited state properties and dynamics. Three excited states on the picosecond, nanosecond and microsecond time scales were observed in all cases, corresponding to 1ILCT, ππ* and 3ILCT respectively.